Micro-arc oxidation surface modified biomedical titanium alloy and preparation method thereof

By forming a porous structured micro-arc oxidation coating on the surface of the titanium alloy, the problem of poor surface hardness and wear resistance of the titanium alloy is solved, significantly improving its friction and corrosion resistance and extending its service life.

CN119307996AActive Publication Date: 2025-01-14SOUTHWEST JIAOTONG UNIV

Patent Information

Application Number
CN202411443430.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-14
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

Titanium alloys have problems with low surface hardness and poor wear resistance in biological medical devices, resulting in insufficient frictional corrosion performance and affecting their service life.

Method used

The porous structure coating with dense and sparse layers is formed on the surface of the titanium alloy by microarc oxidation technology, containing sodium, oxygen, aluminum, phosphorus, potassium and niobium elements. The elements are uniformly distributed and phase composition are ensured through EDS and XRD analysis. Pretreatment and electrolytic reaction parameters are optimized to form an efficient microarc oxidation coating.

Benefits of technology

It significantly improves the microhardness and wear resistance of the surface of titanium alloy, reduces friction corrosion loss, and significantly improves friction corrosion resistance, so that the material can exhibit excellent durability under the combined action of corrosion and wear.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307996A_ABST
    Figure CN119307996A_ABST
Patent Text Reader

Abstract

The invention discloses a micro-arc oxidation surface modified biomedical titanium alloy with good friction corrosion resistance and a preparation method of the micro-arc oxidation surface modified biomedical titanium alloy. The micro-arc oxidation surface modified biomedical titanium alloy comprises a titanium alloy base material and a micro-arc oxidation coating located on the surface of the titanium alloy base material. The micro-arc oxidation coating comprises a compact layer and a sparse layer which are sequentially connected with the titanium alloy base material. EDS element analysis shows that the micro-arc oxidation coating contains a sodium element, an oxygen element, an aluminum element, a phosphorus element, a potassium element, a titanium element and a niobium element. The preparation method comprises the following steps: preparing a micro-arc oxidation electrolyte, wherein the micro-arc oxidation electrolyte comprises sodium titanate, potassium hydroxide, sodium hexametaphosphate and niobium particles; the titanium alloy base material serves as an anode, a stainless steel sheet serves as a cathode, the micro-arc oxidation electrolyte is loaded into an electrolytic cell, then a micro-arc oxidation electrolytic reaction is conducted, and the micro-arc oxidation coating is generated on the surface of the titanium alloy base material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical titanium alloys, and in particular to a biomedical titanium alloy surface-modified by micro-arc oxidation and a preparation method thereof. Background Art

[0002] Titanium alloy TC4 (Ti6Al4V) is widely used in biomedical devices, orthopedic implants and other fields due to its high strength, high biocompatibility, low density and other advantages. However, titanium alloys have the problems of low surface hardness and relatively poor wear resistance. In actual engineering, it has been found that relative movement will occur between titanium alloy connecting parts, causing friction and wear, such as the contact interface of the head and neck parts of artificial hip joints. This damage will evolve into friction corrosion under the action of body fluid corrosion. Friction corrosion refers to the degradation of the material surface caused by the combined action of corrosion and wear. Friction corrosion of titanium alloys will cause surface material loss, deteriorate the service state of components, and even cause component failure. Therefore, it is very important to improve the surface performance of titanium alloys and reduce friction corrosion damage on their surfaces.

[0003] Micro-arc oxidation surface modification technology has the characteristics of simple process, efficient processing, strong controllability, and green environmental protection, and has been widely used in improving the surface properties of titanium alloys. Micro-arc oxidation technology can generate various types of coatings on the surface of titanium alloys by changing the type of electrolyte, thereby giving titanium metal specific surface properties. At present, the existing technology obtains coatings with different properties such as corrosion resistance, wear resistance, and high-temperature oxidation resistance on the surface of titanium alloys by adding different micro-arc oxidation electrolytes. However, the existing technology focuses on the single high-temperature oxidation resistance, corrosion resistance and wear resistance of titanium alloy surface coatings, and the friction corrosion performance of titanium alloys under the combined action of corrosion and wear has not been reported so far. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a biomedical titanium alloy with good friction and corrosion resistance and a micro-arc oxidation surface modified biomedical titanium alloy and a preparation method and a friction and corrosion resistance test method.

[0005] In order to achieve the above object, according to the first aspect of the present invention, a biomedical titanium alloy surface modified by micro-arc oxidation is provided, and the technical scheme is as follows:

[0006] A biomedical titanium alloy with a micro-arc oxidation surface modified includes a titanium alloy substrate and a micro-arc oxidation coating located on the surface of the titanium alloy substrate; the micro-arc oxidation coating includes a dense layer and a sparse layer sequentially connected to the titanium alloy substrate; EDS element analysis shows that the micro-arc oxidation coating contains sodium, oxygen, aluminum, phosphorus, potassium, titanium and niobium.

[0007] As a further improvement of the above-mentioned biomedical titanium alloy surface modified by micro-arc oxidation: the thickness of the dense layer is 7 to 9 μm, and the thickness of the sparse layer is 7 to 9 μm.

[0008] As a further improvement of the above-mentioned biomedical titanium alloy surface modified by micro-arc oxidation: the mass fractions of sodium, oxygen, aluminum, phosphorus, potassium, titanium and niobium in the micro-arc oxidation coating are 0.91%, 43.92%, 8.64%, 1.14%, 0.45%, 29.62% and 15.32%, respectively.

[0009] As a further improvement of the above-mentioned biomedical titanium alloy surface modified by micro-arc oxidation: the micro-arc oxidation coating has a porous structure, the pore diameter is 0.5-4 μm, and the net distance between two adjacent pores is 0.5-3 μm.

[0010] As a further improvement of the above-mentioned biomedical titanium alloy surface modified by micro-arc oxidation: XRD phase analysis shows that the phases contained in the micro-arc oxidation coating include TiO2, Al2TiO5, NbTi4 and Nb2O5.

[0011] As a further improvement of the above-mentioned biomedical titanium alloy with micro-arc oxidation surface modification: the mass fraction of each element in the titanium alloy substrate is: 6.05% aluminum, 3.95% vanadium, 0.11% iron, 0.014% carbon, 0.14% oxygen, 0.006% nitrogen, 0.001% hydrogen, and 89.729% titanium; the tensile strength of the titanium alloy substrate is 860MPa, the yield strength is 795MPa, the elongation is 12%, the elastic modulus is 110GPa, and the Poisson's ratio is 0.3; the surface roughness of the titanium alloy substrate is Ra≤0.1μm.

[0012] In order to achieve the above object, according to the second aspect of the present invention, a method for preparing a biomedical titanium alloy surface-modified by micro-arc oxidation is provided, and the technical scheme is as follows:

[0013] The method for preparing a biomedical titanium alloy with a micro-arc oxidation surface modified as described in the first aspect above comprises the following steps: preparing a micro-arc oxidation electrolyte, wherein the micro-arc oxidation electrolyte comprises sodium titanate, potassium hydroxide, sodium hexametaphosphate and niobium particles; using a titanium alloy substrate as an anode and a stainless steel sheet as a cathode, loading the micro-arc oxidation electrolyte into an electrolytic cell, and then performing a micro-arc oxidation electrolysis reaction, i.e., generating a micro-arc oxidation coating on the surface of the titanium alloy substrate.

[0014] As a further improvement to the above-mentioned method for preparing biomedical titanium alloy with micro-arc oxidation surface modification: the concentrations of the components in the micro-arc oxidation electrolyte are: 5-7 g / L sodium titanate, 3-5 g / L potassium hydroxide, 1-3 g / L sodium hexametaphosphate, and 5-7 g / L niobium particles; the particle size of the niobium particles is 40-60 nm.

[0015] As a further improvement of the above-mentioned preparation method of biomedical titanium alloy with micro-arc oxidation surface modification: the micro-arc oxidation electrolysis reaction adopts a constant voltage mode with a voltage of 350V, a frequency of 500Hz, a duty cycle of 50%, a reaction time of 30min, and an electrolysis temperature of 30°C.

[0016] As a further improvement of the preparation method of the above-mentioned micro-arc oxidation surface modified biomedical titanium alloy, it also includes pretreatment of the surface of the titanium alloy substrate: first, it is polished on a polishing machine with 600#, 1000#, 1500#, and 2000# sandpaper in sequence, and then precision polished using W2.5 diamond grinding paste and a 3000# roughness cloth grinding disc.

[0017] In order to achieve the above object, according to the third aspect of the present invention, a method for testing the friction and corrosion resistance of biomedical titanium alloys surface-modified by micro-arc oxidation is provided, and the technical scheme is as follows:

[0018] The method for testing the friction and corrosion resistance of the biomedical titanium alloy surface modified by micro-arc oxidation described in the first aspect is carried out in a micro-motion test device, using CoCrMo alloy as the counter-friction material, and conducting a friction and corrosion test in simulated body fluid.

[0019] As a further improvement of the test method for the friction and corrosion resistance of the above-mentioned magnetron sputtering modified biomedical titanium alloy: the tensile strength of the CoCrMo alloy is 1507MPa, the yield strength is 962MPa, the elongation is 20%, the elastic modulus is 200GPa, and the Poisson's ratio is 0.3; the mass fraction of each element of the CoCrMo alloy is: chromium element is 28.10wt%, molybdenum element is 5.90wt%, nickel element is 0.88wt%, iron element is 0.65wt%, manganese element is 0.63wt%, silicon element is 0.22wt%, carbon element is 0.25wt%, nitrogen element is 0.12wt%, and cobalt element is 63.25%; the concentration of each component in the simulated body fluid is: Na + 142.0mM, K + 5mM, Mg 2+ 1.5mM, Ca 2+ 2.5mM, Cl - 147.8mM, HCO3 - 4.2mM, HPO4 2-1.0mM, SO4 2- is 0.5mM.

[0020] The present invention has the following beneficial effects:

[0021] Niobium metal has the advantages of stable chemical properties, good biocompatibility, strong corrosion resistance, good high-temperature oxidation resistance, etc. The present invention uses micro-arc oxidation technology to successfully introduce niobium into the surface of a titanium alloy substrate for the first time, forming a niobium-containing micro-arc oxidation coating. The coating is composed of a dense layer and a sparse layer with a porous structure. The thickness and element distribution of the coating are uniform, and there is no crack, delamination or other damage on the surface and the interior, and the coating-substrate bonding is good.

[0022] It has been verified that, compared with the titanium alloy substrate without surface modification, the micro-arc oxidation coating introduced in the present invention can form a new hard phase, reduce the friction coefficient and friction corrosion material loss, open circuit potential change and corrosion current on the surface of the titanium alloy substrate. Therefore, the biomedical titanium alloy with micro-arc oxidation surface modification prepared by the present invention has significantly better microhardness, fretting wear resistance and corrosion resistance, exhibits excellent friction corrosion resistance under the combined action of corrosion and wear, can be used stably for a long time, and has excellent practicality.

[0023] In the above-mentioned friction and corrosion resistance test method, CoCrMo alloy has very high tensile strength and yield strength, which enables it to withstand high loads without plastic deformation during friction. CoCrMo alloy has excellent wear resistance, which is very important for reducing wear between friction pairs. The higher elastic modulus enables CoCrMo alloy to have smaller deformation under load, which improves the stability of the friction pair system. CoCrMo alloy contains higher chromium and molybdenum, which enables the alloy to form a stable passivation film in a corrosive environment, improving its corrosion resistance. The composition design of the simulated body fluid is very close to that of the human body fluid, and can truly reflect the behavior of the material in the actual physiological environment. The simulated body fluid contains a variety of ions (such as Na + , K + Mg 2+ , Ca 2+ These ions can react with the surface of metal materials in complex electrochemical reactions, simulating the corrosion process under actual physiological conditions. It can be seen that the friction and corrosion resistance test method of the present invention can truly and effectively evaluate the friction and corrosion resistance of titanium alloys in actual use environments by using CoCrMo alloy as the wear pair material in the micro-motion test device and conducting friction and corrosion tests in simulated body fluids.

[0024] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. Additional aspects and advantages of the present invention will be partially given in the following description, partially become apparent from the following description, or be learned through the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The drawings constituting a part of the present invention are used to assist in understanding the present invention. The contents provided in the drawings and their related descriptions in the present invention can be used to explain the present invention, but do not constitute improper limitations on the present invention. In the drawings:

[0026] Figure 1 This is a schematic diagram of the structure of the micro-arc oxidation electrolysis device used in the present invention.

[0027] Figure 2 The following is a low-magnification SEM photograph of the surface of the coating-titanium alloy of the present invention.

[0028] Figure 3 This is a high-magnification SEM photograph of the surface of the coating-titanium alloy of the present invention.

[0029] Figure 4 This is a high-magnification SEM photograph of the cross section of the coating-titanium alloy of the present invention.

[0030] Figure 5 This is the EDS surface scan spectrum of the coating-titanium alloy of the present invention.

[0031] Figure 6 This is the EDS line scan spectrum of the coating-titanium alloy of the present invention.

[0032] Figure 7 It is a microhardness comparison diagram of the coating-titanium alloy and the titanium alloy substrate of the present invention.

[0033] Figure 8 The XRD spectrum of the coating-titanium alloy of the present invention is shown in FIG.

[0034] Fig. 9 It is a comparison chart of the friction coefficients of the coating-titanium alloy and the titanium alloy substrate of the present invention.

[0035] Fig.10 It is a comparison chart of the material loss of the coating-titanium alloy and the titanium alloy substrate of the present invention.

[0036] Fig.11 It is a comparison diagram of the open circuit potential of the coating-titanium alloy of the present invention and the titanium alloy substrate.

[0037] Fig.12 It is a comparison diagram of the polarization curves of the coating-titanium alloy and the titanium alloy substrate of the present invention. DETAILED DESCRIPTION

[0038] The present invention is described clearly and completely below in conjunction with the accompanying drawings. A person skilled in the art will be able to implement the present invention based on these descriptions. Before describing the present invention in conjunction with the accompanying drawings, it should be particularly noted that:

[0039] The technical solutions and technical features provided in each part of the present invention, including the following description, may be combined with each other if there is no conflict.

[0040] In addition, the embodiments of the present invention involved in the following description are generally only a part of the embodiments of the present invention, rather than all the embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0041] About the terms and units in the present invention: The terms "include", "have" and any variations thereof in the description and claims of the present invention and related parts are intended to cover non-exclusive inclusions.

[0042] The embodiment of the biomedical titanium alloy surface modified by micro-arc oxidation and the preparation method thereof of the present invention comprises the following steps:

[0043] (1) Pretreatment of titanium alloy substrate

[0044] The mass fractions of the elements in the titanium alloy substrate are: 6.05% aluminum, 3.95% vanadium, 0.11% iron, 0.014% carbon, 0.14% oxygen, 0.006% nitrogen, 0.001% hydrogen, and 89.729% titanium.

[0045] The titanium alloy substrate has a tensile strength of 860 MPa, a yield strength of 795 MPa, an elongation of 12%, an elastic modulus of 110 GPa, and a Poisson's ratio of 0.3;

[0046] The steps of pre-treating the surface of the titanium alloy substrate are: first, polishing with 600#, 1000#, 1500#, and 2000# sandpaper on a polishing machine, and then precision polishing with W2.5 diamond grinding paste and 3000# roughness cloth grinding disc, finally making the surface roughness of the titanium alloy substrate Ra≤0.1μm. Before micro-arc oxidation electrolysis, the titanium alloy substrate is ultrasonically cleaned in anhydrous ethanol for two minutes to remove impurities on the substrate surface, which helps to improve the coating quality.

[0047] (2) Preparation of electrolyte

[0048] A micro-arc oxidation electrolyte is prepared. The micro-arc oxidation electrolyte is an aqueous solution of sodium titanate, potassium hydroxide, sodium hexametaphosphate and niobium particles. The concentrations of the components are: 6 g / L sodium titanate, 4 g / L potassium hydroxide, 2 g / L sodium hexametaphosphate, and 6 g / L niobium particles. The particle size of the niobium particles is 40-60 nm.

[0049] (3) Micro-arc oxidation electrolysis reaction

[0050] Figure 1 Schematic diagram of the structure of the micro-arc oxidation electrolysis device used in the present invention. Figure 1 As shown, the titanium alloy substrate is used as the anode, the stainless steel sheet is used as the cathode, the working distance between the anode and the cathode is maintained at 20 mm, 500 ml of micro-arc oxidation electrolyte is taken into the electrolytic cell, and then the micro-arc oxidation electrolysis reaction is carried out, that is, a micro-arc oxidation coating is generated on the surface of the titanium alloy substrate, and the obtained coating is named as coating-titanium alloy. The coating-titanium alloy is ultrasonically cleaned in anhydrous ethanol for two minutes, and then stored in a sterile drying box at 25°C after drying.

[0051] The micro-arc oxidation electrolysis reaction adopts a constant voltage power supply with a voltage of 350V, a frequency of 500Hz, a duty cycle of 50%, a reaction time of 30min, and an electrolyte temperature of 30°C maintained by a circulation pump and a cooling device. A stirrer is provided in the electrolytic cell.

[0052] Figure 2 The following is a low-magnification SEM photograph of the surface of the coating-titanium alloy of the present invention. Figure 3 This is a high-magnification SEM photograph of the surface of the coating-titanium alloy of the present invention.

[0053] like Figure 2-3 As shown, the surface material of the micro-arc oxidation coating is evenly distributed, with a large number of porous structures, and the surface material is dense. There is no damage such as cracks and delamination between the porous structures, and the surface film quality is good. The pore size is measured to be 0.5-4μm, and the net distance between two adjacent pores is 0.5-3μm.

[0054] Figure 4 This is a high-magnification SEM photograph of the cross section of the coating-titanium alloy of the present invention.

[0055] like Figure 4 As shown, the micro-arc oxidation coating on the surface of the titanium alloy substrate includes a dense layer and a sparse layer sequentially connected to the titanium alloy substrate, wherein the thickness of the dense layer is 7 to 9 μm, and the thickness of the sparse layer is 7 to 9 μm. No obvious cracks were observed on the cross section of the micro-arc oxidation coating, indicating that the micro-arc oxidation coating is well bonded to the titanium alloy substrate.

[0056] Figure 5 This is the EDS surface scan spectrum of the coating-titanium alloy of the present invention.

[0057] like Figure 5 As shown, the EDS element analysis shows that the micro-arc oxidation coating contains sodium, oxygen, aluminum, phosphorus, potassium, titanium and niobium, with mass fractions of 0.91%, 43.92%, 8.64%, 1.14%, 0.45%, 29.62% and 15.32%, respectively. It can be seen that niobium nanoparticles and other electrolytes have been successfully integrated into the micro-arc oxidation coating. At the same time, the micro-arc oxidation coating undergoes a significant oxidation reaction.

[0058] Figure 6 This is the EDS line scan spectrum of the coating-titanium alloy of the present invention.

[0059] like Figure 6 As shown, EDS element analysis shows that the oxygen, niobium, aluminum and titanium elements in the micro-arc oxidation coating are uniformly distributed along the depth direction, and there is an obvious transition of element content between the micro-arc oxidation coating and the titanium alloy substrate, which can enhance the bonding strength between the micro-arc oxidation coating and the titanium alloy substrate.

[0060] Figure 7 It is a microhardness comparison diagram of the coating-titanium alloy and the titanium alloy substrate of the present invention.

[0061] like Figure 7 As shown, after the micro-arc oxidation coating was introduced on the surface of the titanium alloy substrate, the microhardness of the coating-titanium alloy surface increased by nearly 3 times.

[0062] Figure 8 The XRD spectrum of the coating-titanium alloy of the present invention is shown in FIG.

[0063] like Figure 8 As shown, through XRD phase analysis, it is obtained that the micro-arc oxidation coating is composed of TiO2, Al2TiO5, NbTi4 and Nb2O5. It can be seen that Nb nanoparticles will be oxidized to Nb2O5 during the processing.

[0064] An embodiment of the method for testing the friction corrosion resistance of the biomedical titanium alloy modified by micro-arc oxidation surface of the present invention is to use the micro-motion test device disclosed in the Chinese invention patent application with publication number CN108760618A to test the friction corrosion resistance of the coating-titanium alloy and the titanium alloy substrate.

[0065] A copper wire with a length of about 10 cm was welded on the back of the coating-titanium alloy and the titanium alloy substrate to connect the working electrode to study its electrochemical characteristics, and the sample was encapsulated with epoxy resin, leaving only 10 mm 2 research surface.

[0066] The grinding pair material is CoCrMo alloy, which has a tensile strength of 1507MPa, a yield strength of 962MPa, an elongation of 20%, an elastic modulus of 200GPa, and a Poisson's ratio of 0.3; the mass fractions of each element are: 28.10wt% chromium, 5.90wt% molybdenum, 0.88wt% nickel, 0.65wt% iron, 0.63wt% manganese, 0.22wt% silicon, 0.25wt% carbon, 0.12wt% nitrogen, and 63.25% cobalt.

[0067] An electrochemical workstation was used to test the open circuit potential before and after the micromotion test and the polarization curve after the micromotion test. The electrochemical test used three electrodes, with the reference electrode being saturated Ag / AgCl, the counter electrode being a platinum electrode, and the working electrode being a coating-titanium alloy or a titanium alloy substrate.

[0068] The concentrations of the components in the simulated body fluid used are: Na + 142.0mM, K + 5mM, Mg 2+ 1.5mM, Ca 2+ 2.5mM, Cl - 147.8mM, HCO3 - 4.2mM, HPO4 2- 1.0mM, SO4 2- is 0.5mM.

[0069] The micro-motion tangential frequency was set to 1 Hz, the number of cycles was 3000, the sampling rate was 40 Hz, the normal load was 45 N, and the displacement amplitude was 45 μm. The pH of the simulated body fluid was kept at 7.4, and the volume of the corrosion solution required for each experiment was 100 mL.

[0070] Fig. 9 It is a comparison chart of the friction coefficients of the coating-titanium alloy and the titanium alloy substrate of the present invention.

[0071] like Fig. 9 As shown, the micro-arc oxidation coating effectively reduces the friction coefficient of the titanium alloy substrate surface and improves the fretting wear resistance of the coating-titanium alloy surface.

[0072] Fig.10 It is a comparison chart of the material loss of the coating-titanium alloy and the titanium alloy substrate of the present invention.

[0073] like Fig.10 As shown, the introduction of micro-arc oxidation coating can reduce the material loss of coating-titanium alloy by nearly half compared with the material loss of titanium alloy substrate.

[0074] Fig.11It is a comparison diagram of the open circuit potential of the coating-titanium alloy of the present invention and the titanium alloy substrate.

[0075] like Fig.11 As shown in the figure, before the friction starts, the open circuit potential of the coating-titanium alloy is lower than that of the titanium alloy substrate, indicating that the micro-arc oxidation coating reduces the corrosion tendency of the coating-titanium alloy surface. After the friction starts, the material surface is damaged and the open circuit potential decreases, while the decrease in the open circuit potential of the coating-titanium alloy is lower than that of the titanium alloy substrate, indicating that the micro-arc oxidation coating reduces the degree of damage and activity of the coating-titanium alloy surface, thereby enhancing the corrosion resistance.

[0076] Fig.12 It is a comparison diagram of the polarization curves of the coating-titanium alloy and the titanium alloy substrate of the present invention.

[0077] like Fig.12 As shown in the figure, the corrosion voltage of the coating-titanium alloy is -0.243V, and the corrosion current is 1.259μA; the corrosion voltage of the titanium alloy substrate is -0.389A, and the corrosion current is 14.908μA. It can be seen that the introduction of the micro-arc oxidation coating reduces the corrosion current and corrosion voltage values, and improves the corrosion resistance of the coating-titanium alloy surface.

[0078] The above is a description of the relevant contents of the present invention. A person skilled in the art will be able to implement the present invention based on these descriptions. Based on the above contents of the present invention, all other embodiments obtained by a person skilled in the art without creative work shall fall within the scope of protection of the present invention.

Claims

1. A biomedical titanium alloy surface-modified by micro-arc oxidation, comprising a titanium alloy substrate, characterized in that: Also included is a micro-arc oxidation coating located on the surface of a titanium alloy substrate; The micro-arc oxidation coating comprises a dense layer and a sparse layer sequentially connected to the titanium alloy substrate; EDS element analysis revealed that the micro-arc oxidation coating contained sodium, oxygen, aluminum, phosphorus, potassium, titanium and niobium.

2. The biomedical titanium alloy surface modified by micro-arc oxidation according to claim 1, characterized in that: The thickness of the dense layer is 7 to 9 μm, and the thickness of the sparse layer is 7 to 9 μm.

3. The biomedical titanium alloy surface modified by micro-arc oxidation according to claim 1, characterized in that: The mass fractions of sodium, oxygen, aluminum, phosphorus, potassium, titanium and niobium in the micro-arc oxidation coating are 0.91%, 43.92%, 8.64%, 1.14%, 0.45%, 29.62% and 15.32% respectively.

4. The biomedical titanium alloy surface modified by micro-arc oxidation according to claim 1, characterized in that: The micro-arc oxidation coating has a porous structure, the pore diameter is 0.5-4 μm, and the net distance between two adjacent pores is 0.5-3 μm.

5. The biomedical titanium alloy surface modified by micro-arc oxidation according to claim 1, characterized in that: Through XRD phase analysis, it was found that the phases contained in the micro-arc oxidation coating include TiO2, Al2TiO5, NbTi4 and Nb2O5.

6. The biomedical titanium alloy surface modified by micro-arc oxidation according to claim 1, characterized in that: The mass fractions of the elements in the titanium alloy substrate are: 6.05% aluminum, 3.95% vanadium, 0.11% iron, 0.014% carbon, 0.14% oxygen, 0.006% nitrogen, 0.001% hydrogen, and 89.729% titanium. The titanium alloy substrate has a tensile strength of 860 MPa, a yield strength of 795 MPa, an elongation of 12%, an elastic modulus of 110 GPa, and a Poisson's ratio of 0.3; The surface roughness of the titanium alloy substrate is Ra≤0.1 μm.

7. The method for preparing a biomedical titanium alloy surface-modified by micro-arc oxidation according to any one of claims 1 to 6, characterized in that: The following steps are involved: preparing a micro-arc oxidation electrolyte, wherein the micro-arc oxidation electrolyte comprises sodium titanate, potassium hydroxide, sodium hexametaphosphate and niobium particles; With the titanium alloy substrate as the anode and the stainless steel sheet as the cathode, the micro-arc oxidation electrolyte is loaded into the electrolytic cell, and then the micro-arc oxidation electrolysis reaction is carried out, that is, a micro-arc oxidation coating is generated on the surface of the titanium alloy substrate.

8. The method for preparing a biomedical titanium alloy surface-modified by micro-arc oxidation according to claim 7, characterized in that: The concentrations of the components in the micro-arc oxidation electrolyte are: 5-7 g / L sodium titanate, 3-5 g / L potassium hydroxide, 1-3 g / L sodium hexametaphosphate, and 5-7 g / L niobium particles; the particle size of the niobium particles is 40-60 nm.

9. The method for preparing a biomedical titanium alloy surface-modified by micro-arc oxidation according to claim 7, characterized in that: The micro-arc oxidation electrolysis reaction adopts a constant voltage mode, with a voltage of 350V, a frequency of 500Hz, a duty cycle of 50%, a reaction time of 30min, and an electrolysis temperature of 30°C.

10. The method for preparing a biomedical titanium alloy surface-modified by micro-arc oxidation according to claim 7, characterized in that: It also includes pre-treatment of the titanium alloy substrate surface: first, it is polished on a polishing machine with 600#, 1000#, 1500#, and 2000# sandpaper in sequence, and then precision polished using W2.5 diamond grinding paste and a 3000# roughness cloth grinding disc.

Citation Information

Patent Citations

  • Fretting test device

    CN108760618A

  • Method for preparing biological ceramic membrane layer on titanium alloy surface through graded combined oxidation in stages

    CN104988558A

  • Surface treatment for improving bioactivity and wear-resistant ability of titanium alloy surfaces

    CN1712076A

  • Electrolyte for forming black ceramic coat on rectifying metals and their alloys; method of forming such coat and coat formed by this method

    RU2285066C1

  • Electrolyte for preparing hierarchical structure porous coating on titanium alloy surface by micro-arc oxidation

    WO2021031548A1

Cited By

  • Micro-arc oxidation coating for artificial hip joint Ti6Al4V alloy and preparation method of micro-arc oxidation coating

    CN120485916A